Greenwashing Practices and its Consequences in Hospitality Industry: A Systematic Literature Review - Adhikari, Ujjwal (Janaprakash Journal of Multidisciplinary Research, 2024)
Companies are using green marketing approaches to convey their environmental initiatives, aiming to enrich their competitive advantage and attract consumers with ecological awareness, however they do not satisfy such standards. Interest in greenwashing has increased over the past few decades. Nevertheless, there is still a need for thorough and systematic research focused on the development of this phenomenon and its effects on stakeholders. This study aims to offer a comprehensive overview and synthesis of the current knowledge on greenwashing by conducting a bibliometric analysis of articles published until 2024. It highlights the most significant research in this area, with a particular focus on recent articles connecting greenwashing to green marketing, and identifies gaps and opportunities for future research. This study analyze the greenwashing practices in the marketing area especially in the hospitality industry using the tool Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) and bibliometric methods. This analysis was conducted using the Web of Science databases, resulting in 40 relevant articles identified following the PRISMA protocol. VOSviewer software was used for generating network maps. Literature review matrix was designed using MS-Excel software. The result from bibliometric study indicate that the concept of greenwashing has gained significant attention, with an increasing number of studies published in recent years. Majority of reviewed literature revealed that greenwashing severely damages brand attitude, brand trust and consumer loyalty in marketing sector. It also demonstrates the negative impact on consumer repurchase intention and willingness to pay. Greenwashing leads to consumer confusion, skepticism, and perceived risk, reducing trust in green products. However, vague claims may have a slight positive effect on marketing. The study highlights the practical steps for industry leaders to counteract the negative effects of greenwashing on consumer behavior, particularly within the hospitality sector, by maintaining customer loyalty and mitigating adverse effects on repurchasing intentions.